Field testing of a DVB-SH waveform in Japan - Heuberger, Albert; et al. (Proceedings, 4th IEEE International Symposium on Broadband Multimedia Systems and Broadcasting, 2009)
Intensive efforts are under way to validate the DVB-SH waveform in field tests. This paper focuses on the validation of satellite-only broadcasting in urban and suburban environment. The performance of a single carrier QPSK and multicarrier OFDM waveform transmitted from a high power SBand satellite is studied for different Forward Error Correction schemes. The Quality-of-Service is evaluated for error protection both on Physical Layer (Class 2) and for error protection on Link Layer (Class 1). The results show that it is possible to operate an OFDM waveform from a high-power broadcasting satellite. The QoS in the urban and suburban routes is 85 % for error protection on Physical Layer and at best 70 % for error protection on Link Layer. These results indicate that Class 2 DVB-SH receivers can provide good QoS even in urban center
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.komele.fieldt
Keywords: DVB-SH; Mobile satellite broadcasting; Mobile TV; OFDM over satellite; Quality-of-service